The impacts of human migration and city lockdowns on specific air pollutants during the COVID-19 outbreak: A spatial perspective - Zeng, Jingjing (J Environ Manage, 2021)
The outbreak of COVID-19 continues to bring unprecedented shock to mankind's socioeconomic activities, and to the wider environment. China, as the early epicenter of the pandemic, locked down one-third of its cities in an attempt to prevent the rapid spread of the virus. Human migration patterns have subsequently been radically altered and many regions have seen perceived improvements in air quality during the lockdowns. This study empirically examines the relationship between human migration and air pollution and further evaluates the causal impacts of the lockdowns. A spatial econometric method and a spatial explicit counterfactual framework are employed in this study. The key findings are as follows: i) a considerable amount of variation in AQI, PM(10), PM(2.5), and NO(2) concentration can be explained by human migration but we fail to find suggestive evidence in the cases of SO(2) and CO; ii) the implementation of lockdown measures led to a significant reduction in AQI (18.1%), PM(2.5) (22.2%), NO(2) (20.5%), and PM(10) (10.7%), but has no meaningful impacts on SO(2,) CO and O(3) levels; iii) further analysis indicates that the impacts of lockdown policies varied by control stringency and by regional heterogeneity. Our findings are of great importance for the Chinese government to create a stronger and more coherent framework in its efforts to tackle air pollution.